IoT Based Solar Automatic Clothes Hanger System - Nik Muhammad Imam Nik Abdul Khalid; Bakar, Lilywati (Progress in Engineering Application and Technology, 2024)
Laundry tasks are commonly performed as part of the daily routine, posing a challenge for individuals with time constraints, especially those engaged in busy daily schedules. This project endeavors to create an automated cloth hanger system that responds to weather changes, aiding users in managing laundry, particularly during rainy days. Controlled by the NodeMCU ESP32 microcontroller, the cloth hanger incorporates three sensors: a rain sensor, LDR, and DHT sensor. Additionally, a solar energy system is introduced to sustainably charge the lead-acid battery, powering the entire cloth hanging system with environmentally friendly technology. The DC motor's movement is guided by feedback signals from the sensors, detecting rain, low light levels, and high humidity. In response to any of these signals, the system automatically shelters the clothes. Through analysis, the prototype system accommodates a maximum of six clothes on the hanger and provides smartphone notifications. A fully charged 12 V/7.2 Ah Sealed Lead Acid battery can support the maximum load under normal conditions for 24 hours without requiring recharging. In conclusion, the automated cloth hanger system has been successfully developed to streamline daily laundry tasks, incorporating green technology features.